Pengaruh Supporting Electrolyte terhadap Deteksi Ion Logam Cr(VI) Menggunakan PLE Termodifikasi Lapisan Tipis Perak dengan Metode Voltammetri - Putri, Nella Aulia; Sari, Trisna Kumala (MASALIQ, 2025)
Chromium (VI) ions are recognized for their toxicity, mutagenicity, and carcinogenic properties, posing significant risks to both human health and the environment. This study aims to optimize the conditions of supporting electrolytes for the electrochemical detection of Cr(VI) ions using a Pencil Lead Electrode (PLE) modified with a thin layer of silver (Ag/PLE). Employing cyclic voltammetry, we investigated the modification of the PLE and analyzed the effects of varying supporting electrolytes on the detection sensitivity of Cr(VI) ions. Our findings indicate that a 0.1 M HNO3 solution serves as the optimal supporting electrolyte, with oxidation and reduction potentials recorded at +1.4287 V and +0.3906 V, respectively. The observed differences in the sensitivity of Cr(VI) detection can be attributed to the varying diffusion rates of the analyte across the electrode surface. This study presents a straightforward, sensitive, and cost-effective electrochemical method for detecting Cr(VI) ions, offering significant implications for environmental monitoring and public health safety. By enhancing detection methodologies, this research contributes to the broader discourse on mitigating the adverse effects of hazardous metal ions in ecological systems.